Risk factors for intensive care admission in patients with COVID-19 pneumonia: A retrospective study - Abdullah Mobeireek; Saud AlSaleh; Loui Ezzat; Osama Al-saghier; Sultan Al-Amro; Abdulla Al-Jebreen; Armen Torchyan; Mohammed AlHajji; Liju Ahmed (Journal of Infection and Public Health, 2023)
Background: Coronavirus disease 2019 (COVID-19)-associated mortality is predominantly due to respiratory failure. However, risk factors and predictive models for disease progression in patients with COVID-19 are not consistent across the globe. In this study, we aimed to assess the risk factors associated with intensive care (ICU) admission and mortality in patients with COVID-19 pneumonia. Methods: Information was retrieved from the database of all patients admitted with COVID-19 pneumonia between March 2020 and July 2020 at a tertiary care center in Saudi Arabia. The patients’ demographic, clinical, laboratory and radiological characteristics were analyzed. Results: Of 1054 patients admitted with PCR proven COVID-19, 254 patients (24%) with radiological evidence of pneumonia were enrolled. The median age was 55, with 25.6% above 65 years and 55.1% males. The comorbidities included hypertension (45%), diabetes (43%), dyslipidemia (24%), solid organ and bone marrow transplantation (14.5%), malignancy (13.4%), ischemic heart disease (10.6%) and chronic kidney disease (9.4%). The mortality rate was 4.7%, and 22.8% were admitted to the ICU.The risk factors for ICU admission were> 65 years of age (RR: 1.74, CI 95%, 1.10–2.74, p = 0.017), diabetes melitus (RR: 1.66, CI 95% 1.06–2.62, p = 0.028), heart failure (RR: 2.51, CI 95%, 1.28–4.93, p = 0.007), respiratory rate> 25 (RR: 2.75, CI 95%, 1.66–4.55, p < 0.001), upper lobe involvement (RR: 1.68, CI 95%, 1.02–2.77, p = 0.043), and C-reactive protein (CRP)> 140 (RR: 1.89, CI 95%, 1.14–3.13, p = 0.013).The risk factors for mortality were> 65 years of age (RR: 5.82, CI 95%, 1.81–18.68, p = 0.003), upper lobe involvement on chest radiography (RR:4.40, CI 95%, 1.22–15.86, p = 0.016), diffuse chest computed tomography changes (RR: 7.36, CI 95%, 2.31–23.46, p < 0.011), ischemic heart disease (RR: 4.20, CI 95%, 1.36–13.04, p = 0.028), chronic kidney disease (RR: 6.85, CI 95%, 2.35–19.90, p < 0.003), cerebrovascular disease (RR:13.61, CI 95%, 5.01–36.96 p < 0.001), respiratory rate> 25 (RR: 3.94, CI 95%, 1.32–11.78 p = 0.023), oxygen saturation< 90% on admission (RR: 12.19, CI 95%, 3.71–40.01, p < 0.001), thrombocytopenia (RR:4.16, CI 95%, 1.37–12.64, p = 0.013), and elevated troponin (RR: 6.20, CI 95%, 1.73–22.24, p = 0.003). Conclusions: In this study, nearly a quarter of the patients with COVID-19 pneumonia required intensive care. We identified several risk factors associated with ICU admission and mortality that may be useful for predicting, triaging, and managing COVID-19 pneumonia patients. However, these findings need to be validated prospectively.